Wrist singularity avoidance with a robot end-effector adding an oblique, redundant axis. (August 2021) - Milenkovic, Paul
Highlights: Exploits symmetry axis of tip of curved welding tool for singularity avoidance. Extends high-order path-following method to control tool roll about this axis. Encounters wrist singularity with exact tool tip position and pointing direction. Also limits joint rate and acceleration at constant rate of tool traversal. Finds paths meeting these conditions with varying and with constant tool roll. Abstract: Novel high-order procedures follow finite displacements avoiding the adverse effects of the wrist singularity of a serial robot manipulating a curved tool. In robotic welding, this type of end effector is commonly applied to right-angle seams. This tool is symmetric about a line emanating from its tip, which adds an effective revolute-joint axis line to the robot. The curve in the tool places this axis line oblique to the third joint in the robot wrist. When the second wrist axis is out of the plane containing the third joint and tool axes, the tool axis supplies useful kinematic redundancy for mitigating the loss of mobility in a 3-axis wrist on approach to its singularity. A new method plans a path encountering the wrist singularity while satisfying limits on joint rate and acceleration under a constant rate of tool traversal. This method maintains precise position of the tool tip with the seam while allowing rotation of the tool about its symmetry axis. This is accomplished with either zero or nearly zero deviation in pointing direction.